(untitled) (Interdisciplinary Journal of Nursing and Health, 2024)
Background: Time is the most crucial prognostic factor in out-of-hospital cardiac arrest (OHCA) owing to its clinical features. Dispatcher-assisted CPR (DA-CPR) by dispatch centers to a bystander calling for an ambulance, enabling even an inexperienced bystander to start CPR in 50% of cases and reducing the free therapy interval from chest compression to less than three minutes. Objectives: to assess the dispatch-assisted cardiopulmonary resuscitation performance during out-of-hospital cardiac arrest. Methods: a retrospective study was conducted at the Firenze-Prato Emergency Operation Centre to analyse data collected from all dispatch audio recordings of OHCA events that occurred between 1 January 2019 and 31 December 2020. Emergency calls lasting less than 60 s were excluded from the analysis, as this duration does not provide dispatchers with adequate time to accurately identify OHCA and provide pre-arrival instructions to the bystander. Results: A total of 1,267 OHCAs cases were included in this study, with 832 (65.7%) occurring in 2019 and 435 (34.3%) in 2020. Emergency nurses offered pre-arrival instructions in 272 cases (21.5%), with 160 cases in 2019 (19.2%) and 112 cases (25.7%) in 2020 (c2=7.19, p=0.007). These instructions were accepted by the caller in 9% (n=75) and 14% (n=61) of the cases, respectively (c2=7.48, p=0.006). OHCA events that could not be identified by telephone (therefore, DA-CPR was not possible) were 365 cases (43.9%) in 2019 and 175 cases (40.2%) in 2020 (c2=1.55, p=0.213). Conclusions: The adoption of a standardised protocol for delivering pre-arrival instructions, along with training programs focusing on OHCA and interview techniques, is strongly recommended based on the findings of our study. This was reinforced by the analysis of nighttime calls during which DA-CPR was not provided, including cases without clear justification.